How can we Agree on Anything in This Environment? Tunisian Media, Transition and Elite Compromises: A View From Parliament. (October 2021) - Cavatorta, Francesco; Mekki, Nidhal
The literature on the role of the media during processes of transitions to democracy is divided over the positive or negative influence media outlets have. Both theoretically and empirically cases can be substantiated. In the case of the 2011 Arab revolts, however, there is a scholarly consensus that the media—traditional and social—have negatively affected the processes of transitions. While the criticism of the role of the media is empirically borne out, it does not explain how Tunisia was able to consolidate its democracy despite a polarizing media environment. Based on participant observation and interviews, the article argues that the inner workings of the Constituent Assembly and the role of individual deputies were crucial in overcoming a hostile atmosphere. This suggests that the role of political actors in negotiating the new rules of the game is more important than other factors shaping a transition.